Iridium Oxide pH Sensor Based on Stainless Steel Wire for pH Mapping on Metal Surface - Shahrestani, S. (Institute of Physics Publishing, 2018)
A simple technique to fabricate the iridium oxide pH sensor is useful in several applications such as medical, food processing and engineering material where it is able to detect the changes of pH. Generally, the fabrication technique can be classified into three types: electro-deposition iridium oxide film (EIrOF), activated iridium oxide film (AIROF) and sputtering iridium oxide film (SIROF). This study focuses on fabricating electrode, calibration and test. Electro-deposition iridium oxide film is a simple and effective method of fabricating this kind of sensor via cyclic voltammetry process. The iridium oxide thick film was successfully electrodeposited on the surface of stainless steel wire with 500 cycles of sweep potential. A further analysis under FESEM shows detailed image of iridium oxide film which has cauliflower-liked microstructure. EDX analysis shows the highest element present are iridium and oxygen which concluded that the process is successful. The iridium oxide based pH sensor has shown a good performance in comparison to conventional glass pH sensor when it is being calibrated in buffer solutions with 2, 4, 7 and 9 pH values. The iridium oxide pH sensor is specifically designed to measure the pH on the surface of metal plate. Â© Published under licence by IOP Publishing Ltd.